Determination of Potassium (K) in Green Coconut (Cocos viridis) from Dolo and Labuan areas using Spectrophotometry - Hikmawandari, Hikmawandari; Ningsih, Purnama; Ratman, Ratman (Universitas Tadulako, 2019)
One of the potential plantations in Dolo and Labuan area is coconut plant. Coconut water as one of the coconut product has not been widely used, even it contains many minerals. Potassium contained in coconut water can be utilized an additional mineral intake for human. This study aimed to determine potassium (K) levels in green coconut (coconut viridis) water from Dolo and Labuan areas using spectrophotometric. The results showed that the average concentration of K in green coconut water samples from Dolo area was 162 ppm, while from Labuan area was 154 ppm. This study concluded that the higher level of potassium is in green coconut water samples from Dolo area.